Studies of the comparative efficacy of alcoholic extracts of Bironja, Turmeric, and Veranda leaves with that of patent drug Nilzan against Nematodiasis in sheep (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
The objectives of this study was to determine the comparative efficacy of some indigenous plants (Bironja, Turmeric and Verenda leaves) with that of patent drug Nilzan against Nematodiasis in sheep. Out of 85 sheep of indigenous breed 75 sheep which were suspected to be suffering from nematode, aged 2- 3 years and weighing about 10-12 kg were used for this study. The sheep were divided into 15 equal groups (Group A, B, C, D, E, F, G, H, I, J, K, L, M, N and O). The collected Bironja, Turmeric and Verenda leaves were cut into small pieces and sun dried for 7 days followed by drying separately in a hot air woven at 45°C for 6 hours. Then alcoholic extracts of selected medicinal plants were prepared by mixing 100 gm of each grinded powdered sample with 250 ml of alcohol and kept in separate air tight bottle and labeled for further study. Administration of three different doses of powdered Bironja (3, 6 & 9 ml /kg body wt), Turmeric  (2, 4 & 6 ml /kg body wt) and Verenda leaves (2, 4 & 6 ml /kg body wt) showed 13-40% , 11-15% and 4-7% efficacy respectively against nematodes in sheep. Administration of Nilzan (30 mg/kg body wt) orally was highly effective (73-89%) against all the species of nematodes in sheep. Among medicinal plants Bironja was found to be most effective followed by turmeric. Veranda leaves were found to be totally ineffective against nematodes in sheep. No significant change was observed following treatment with Bironja seeds, Turmeric, Verenda leaves and Nilzan on serum glucose and SGPT in sheep. Haematological parameters were not significantly altered following any of the doses of three medicinal plants and Nilzan in sheep.Asian Australas. J. Biosci. Biotechnol. 2017, 2 (1), 29-36